Pancreatic Configuration Index in Predicting Postoperative Pancreatic Fistula in a Tertiary Care Center in Nepal - Shah, Surendra; Ghimire, Bikal; Paudel, Sharma; Singh, Yogendra Prasad (Journal of Nepal Health Research Council, 2020)
Background: Post-operative pancreatic fistula is the single most common and most significant cause of post-operative morbidity and perioperative mortality. Identification of at risk patient preoperatively help to take policy of extra vigilance to act on time. This study evaluated the predictive role and cut-off value of pancreatic configuration index to predict post-operative pancreatic fistula.Methods: This was a prospective observational study in patients who had undergone pancreaticoduodenectomy from March 2017 to June 2018 at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The patients with age <16 years, those who underwent re-exploration or mortality before 3rd postoperative day, additional surgery besides pancreaticoduodenectomy were excluded from the study. Pancreatic configuration index was calculated as a ratio of pancreatic parenchymal thickness and pancreatic duct diameter. Predictive value of pancreatic configuration index in predicting post-operative pancreatic fistula was evaluated.Results: Among 58 patients, 9 were excluded from study and 49 patients were included in the study. The mean age of the patients was 56.6 ± 13.9 years (21 to 79 years) and male to female ratio was 1.1:1 (26 vs 23). Post-operative pancreatic fistula developed in 13/49 (26.5%) patients. On both univariate and multivariate analysis, pancreatic texture (p = 0.022), main pancreatic duct diameter at neck (p = 0.002) and pancreatic configuration index (p = 0.001) were significantly associated with development of post-operative pancreatic fistula. The sensitivity and specificity of pancreatic configuration index to predict post-operative pancreatic fistula are 92.3% and 91.7% with positive predictive value of 80% and negative predictive value of 97.1%.Conclusions: Pancreatic configuration index is a useful preoperative predictor of post-operative pancreatic fistula after pancreaticoduodenectomy.Keywords: Pancreaticoduodenectomy; pancreatic configuration index; postoperative pancreatic fistula.